2021
DOI: 10.1177/15346501211041407
|View full text |Cite
|
Sign up to set email alerts
|

Parent-Mediated Home Intervention for Delayed Sleep-Onset and Night Waking in a Child With Autism Spectrum Disorder

Abstract: We report the case of a 10-year-old boy with autism spectrum disorder who had difficulty initiating and maintaining sleep. Through home consultation, his parents were trained to implement a multicomponent sleep intervention that included (a) faded bedtime, (b) regimented pre-bedtime routines, and (c) elimination of positive social consequences contingent on sleep problems including unwanted co-sleeping. A critical element in the case was functional assessment of the conditions associated with poor sleeping and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The American Academy of Pediatrics recommends that school-aged children receive between 8 and 10 hrs of sleep per night (Paruthi et al, 2016). Sleep disorders are, unfortunately, common within the pediatric population (Del Rosso et al, 2021; Linnehan et al, 2021). Del Rosso and colleagues reported approximately 20–40% of school-age children experience sleep disturbance.…”
Section: Theoretical and Research Basis For Treatmentmentioning
confidence: 99%
“…The American Academy of Pediatrics recommends that school-aged children receive between 8 and 10 hrs of sleep per night (Paruthi et al, 2016). Sleep disorders are, unfortunately, common within the pediatric population (Del Rosso et al, 2021; Linnehan et al, 2021). Del Rosso and colleagues reported approximately 20–40% of school-age children experience sleep disturbance.…”
Section: Theoretical and Research Basis For Treatmentmentioning
confidence: 99%
“…Specifically, telehealth-mediated services increase access to services by building capacity within families to deliver behaviorally based challenging behavior treatment through evidence-based caregiver training and coaching. Recent research has shown that tele-delivered training that includes components of behavioral skills training, and in-vivo coaching is effective in training caregivers to implement behaviorally based treatment with fidelity (Drew et al, 2022a;Drew et al, 2022b) and improving behavioral outcomes for children with ASD (Lindgren et al, 2016;Linnehan et al, 2022;Neely et al, 2021;Suess et al, 2014;Tomlinson et al, 2018). The extant data on telehealth behaviorally based challenging behavior treatment indicate that telehealthmediated services hold promise for improving both access to and quality of challenging behavior treatment for individuals with ASD.…”
mentioning
confidence: 99%